THE USAGE OF METAPHOR IN A CUP OF TEA BY KATHERINE MANSFIELD (American Journal of Research in Humanities and Social Sciences, 2024)
This paper analyzes the effective usage of metaphor in Katherine Mansfield's short story "A Cup of Tea." Metaphor, as a literary device, plays a significant role in conveying complex emotions, ideas, and themes in Mansfield's work. By examining specific examples of metaphorical language in the story, this analysis aims to shed light on the deeper layers of meaning and enhance our understanding of Mansfield's narrative technique. The paper explores how metaphors are employed to portray the characters' inner thoughts and desires, depict social dynamics, and underscore the story's central themes of wealth, class, and human connection. Moreover, it highlights the nuanced ways in which metaphorical language enhances the reader's engagement with the text and contributes to the overall literary experience.